Biodeterioration of ancient monuments: Problems and prospects - Jaiswal2, Kavita Sharma1, Megha Agrawal1; A. K. (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Fungal ability in production of pigments and organic acids have crucial role in discoloration and degradation of different types of stone in cultural heritage objects. Additionally, stone objects may support novel communities of microorganisms that are active in biodeterioration process. The air contains a large amount of biological and a biotic component such as, pollen grains, fungal spores, insects, mites, fibers and dust particles but their number and concentration depend upon the geographical location, types of vegetation and meteorological parameters. The problem of deterioration of ancient monuments caused by microbial agent, of which fungi play an important role in the deterioration. Present investigation focuses on mycobial survey of the Temple of Sirpur and study carried out March 2010 to February 2011. During the investigation period 18 fungal species were isolated from the surface of different ancient monuments of Sirpur which are Aspergillus, Penicillium, Curvularia, Cladosporium, Fusarium and Rhizopus reported as dominant fungal type in Laxman tample of Sirpur.<span style="font-size: 12pt; color: black; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">